2005
DOI: 10.1385/ep:16:4:355
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in Craniopharyngiomas: Microvascular Density and Tissue Expression of the Vascular Endothelial Growth Factor (VEGF) and Endostatin

Abstract: Craniopharyngiomas are benign tumors of the sellar region generally associated with endocrine abnormality and often locally aggressive. Several studies have demonstrated that angiogenesis or neovascularization plays an important role in tumoral growth. The microvascular density (MVD) of craniopharyngiomas was determined in tumor tissue samples from a reference neurosurgery center located in southern Brazil using immunohistochemical methods for two endothelial markers, CD34 and CD105 (endoglin). In addition, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…By contrast, it is only weakly expressed or absent in the vessels of normal tissues 32 . Thus it represents a powerful marker of neovascularization in various types of tumors 10,33–36 . CD105 was chosen for MVD assessment in this study since tumor MVD quantified through this marker has already been demonstrated to better reflect effective tumor neo‐angiogenesis in meningiomas in comparison to panendothelial markers, 8 such as CD34, which was used in the other correlative studies between MVD and tumor cell‐derived cav‐1 expression 3,4,28 …”
Section: Discussionmentioning
confidence: 99%
“…By contrast, it is only weakly expressed or absent in the vessels of normal tissues 32 . Thus it represents a powerful marker of neovascularization in various types of tumors 10,33–36 . CD105 was chosen for MVD assessment in this study since tumor MVD quantified through this marker has already been demonstrated to better reflect effective tumor neo‐angiogenesis in meningiomas in comparison to panendothelial markers, 8 such as CD34, which was used in the other correlative studies between MVD and tumor cell‐derived cav‐1 expression 3,4,28 …”
Section: Discussionmentioning
confidence: 99%
“…Through the 8-cell stage the blastomeres of murine embryos are totipotent ( 46 – 48 ). The cell cycle of the two-cell embryos in the mouse has duration of 20–26 h with G 1 and S phases that last ∼1–2 and 6–7 h; these phases are followed by an extended G 2 phase (12–15 h) and M (mitosis) phase of 1–2 h ( 49 ). Many plant extracts have been used as a source of medicinal agents to cure urinary tract infections, cervicitis vaginitis, gastrointestinal disorders, respiratory diseases, cutaneous problems, helmintic infections, parasitic protozoan diseases, and antitumor and antimicrobial ( 17 , 50 – 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…2,13,51,[55][56][57] One functional study using a corneal angiogenesis assay revealed that recurrent ACP samples had a significantly higher angiogenic potential than nonrecurrent ACP, but less than glioblastoma multiforme or arteriovenous malformations. 51 Imatinib-loaded microspheres reduced neovascularization in this model, but the use of this or other antiangiogenic approaches in patients has not been reported in the literature.…”
Section: Molecular Biology Of Tumor-associated Angiogenesismentioning
confidence: 99%